Developing English Textbook for Pre-school Children - Munir, Sirajul; Warmansyah, Jhoni (Journal of English Education and Teaching, 2023)
This present research is motivated by lack of English teaching materials for pre-school children and the need for an appropriate English textbook. The aim of this research is to develop an English textbook for English for pre-school children. This research adopted Research and Development which employed three stages, namely exploration stage, design stage, and validation stage. Data were collected through document analysis and interviews. The result of need analysis pointed out that pre-school teachers need an English textbook for teaching. In the design phase, the textbook is carefully designed to meet the teachers and children’s need. The textbook includes topics related to children’s real life such as greeting, alphabet, numbers, colors, fruits, animals, family, day, and month. Whereas the activities are designed joyfully. For example, matching the words, drawing pictures, finding pictures that are different, cutting, and so on. The textbook also used colorful images to attract students’ attention to read and to stimulate their knowledge. The textbook was deemed valid. Considering these findings, the English textbook could be used in teaching English for pre-school children.Keyword: English textbook, teaching English, pre-school children